Pouk v šolski knjižnici - s 5. razredom o ljudskih pravljicah - Škrlj, Gregor (Šolska knjižnica, 2016)
The paper presents the implementation of a library and information knowledge (KIZ) lesson in connection with folk tales in the 5th grade. Folk tales are a topic of many lessons since the first grade onward. During this lesson, the pupils came to know the Jaga baba folk tale in a slightly different way than usual - through a party game, by watching a video, and by filling out a handout. During the lesson, we once again went over the layout of material in the library, pointed out folk literature in particular, and revised how pupils can find a specific tale on the shelf and in individual collections of tales. Afterwards, the pupils did just that and presented the tale they had found to their classmates in an oral presentation. The pupils loved it because they were able to choose folk tales from various countries and use them to present the country, its customs and language.
Keywords: bibliopedagoško delo; ljudsko slovstvo; osnovne šole; slovenske ljudske pravljice; šolske knjižnice